A Legal Analysis of the Limitations on the Application of Restorative Justice in the Resolution of Sexual Violence Crimes - Racha Gusty Recoba Satya Nugraha; Ali Masyhar; Cahya Wulandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the juridical limitations governing the application of restorative justice in the resolution of sexual violence crimes within the Indonesian criminal justice system. The research employed a nonempirical normative legal method with descriptive analytical orientation through statutory, conceptual, and case approaches. Primary legal materials consisted of Indonesian criminal legislation, restorative justice regulations, and judicial decisions, while secondary materials were derived from scholarly doctrines and peer reviewed legal studies concerning victim protection and restorative justice theory. The findings indicate that significant normative inconsistencies persist between restorative justice policies and statutory provisions emphasizing victim protection, legal certainty, and public accountability in sexual violence cases. The absence of explicit legal boundaries regarding the admissibility of restorative mechanisms has generated interpretative disparities among law enforcement institutions and increased the risk of coercive settlement practices influenced by unequal power relations and social pressure. The study further demonstrates the necessity of reconstructing criminal law policy through harmonized regulations, offense classification standards, verified victim consent mechanisms, and institutional supervision to ensure that restorative justice remains compatible with the protection of victims and the objectives of modern criminal law reform in Indonesia.